ANALISIS HUBUNGAN ANTARA KEPEMILIKAN SAHAM MINORITAS DAN DIVIDEND PAY OUT RATIO DENGAN LABA DAN INVESTMENT OPPORTUNITY SET SEBAGAI VARIABEL MODERASI - NURWULANDARI, ANDINI (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 5 No 1 (2010), 2010)
This research investigates issue of protection for minority shareholders of Indonesian public companies. Specifically, the research examines relationship between minority shareholders and dividend pay out ratio with earnings and investment opportunity as moderating variables. Research population includes non monetary companies listed on JSX in 2002, 2003, and 2004. Sample is gathered by purposive sampling method, that is companies distributing dividend in 2002 (55 companies), 2003 (67 companies), and 2004 (75 companies). Multiple regression and logistic regression model are used to analyze data. The result reveals that positive impact of minority shareholders on DPR is due to their interests is unwell protected. Further more, they are also not able to influence dividend distribution decision when companies earn profit.
Keywords: minority shareholders, corporate governance, dividend pay out ratio.